Achievement Level of Students Who Join the HMI Organization - Darisman Solin; Fauzi Saleh; Musdawati (Winaya Inspirasi Nusantara Foundation, 2021)
This research answers the formulation of the problem, namely: 1. How is the level of achievement of students in FUF and FTK UIN Ar-Raniry who follow the HMI organization, 2. What are the supporting factors for student achievement in FUF and FTK UIN Ar-Raniry who follow the HMI organization, 3. What are the inhibiting factors for student achievement in FUF and FTK UIN Ar-Raniry who follow the HMI organization and their solutions. The data collection techniques used in this research are Library Research (library data), namely: research conducted by collecting library data, this is done to get theories that are closely related to this research and to see previous research, and Field Research, namely: research conducted to obtain primary data related to research, by using a questionnaire. The results of this study are the average grade point average of all respondents for each semester has increased positively. Based on the documentation data, it was found that in the middle of the management, the respondents experienced an increase in the achievement index. Whereas in the following semester, the respondent's achievement index decreased but was still higher than the achievement index from the beginning of the management. Supporting factors for FUF and FTK UIN Ar-Raniry students who join the HMI organization include internal factors consisting of intelligence, motivation, talent, health, psychology, and achievement maturity.